2009
DOI: 10.1038/cdd.2009.86
|View full text |Cite|
|
Sign up to set email alerts
|

Cyclin D1 promotes anchorage-independent cell survival by inhibiting FOXO-mediated anoikis

Abstract: O-class forkhead box (FOXO) transcription factors are critical regulators of diverse cellular processes, including apoptosis, cell-cycle arrest, DNA damage repair and oxidative stress resistance. Here, we show that FOXO1 and FOXO3a have an essential function in promoting cell detachment-induced anoikis, resistance to which is implicated in cancer development and metastasis. In contrast, the oncoprotein cyclin D1 inhibits anoikis. We further show that cyclin D1 interacts with FOXO proteins and impedes their tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…Figure 5d shows that Matrigel weakened Bim accumulation. As in previous studies, the failure of Bim to accumulate corresponds with a failure to proceed with anoikis [24,25]. This finding also explains how Matrigel reverses the selective effect of anoikis in the fluorescence microscopy assay in which cells encounter less apoptosis stress in the presence of Matrigel; therefore, the survival advantage brought about by exogenous Pokemon would not be achieved.…”
Section: Resultssupporting
confidence: 79%
“…Figure 5d shows that Matrigel weakened Bim accumulation. As in previous studies, the failure of Bim to accumulate corresponds with a failure to proceed with anoikis [24,25]. This finding also explains how Matrigel reverses the selective effect of anoikis in the fluorescence microscopy assay in which cells encounter less apoptosis stress in the presence of Matrigel; therefore, the survival advantage brought about by exogenous Pokemon would not be achieved.…”
Section: Resultssupporting
confidence: 79%
“…2D (middle), Runx2 proteins were specially pulled down by GST-FOXO1 fusion protein FO1-2, which contains amino acids from 149 to 267 in FOXO1. The same region of FOXO1 has been shown to interact with other proteins such as cyclin D1 (39), suggesting that FO1-2 may act as a functional motif that interacts with other proteins. Collectively, both co-immunoprecipitation and GST pull-down assay demonstrated that FOXO1 interacts with Runx2 in vitro and in PCa cells.…”
Section: Resultsmentioning
confidence: 99%
“…The Trop-2 transcription control network, including factors activating Trop-2 expression or downstream growth-stimulatory pathways has been recently reported [46]. Interestingly, Trop-2-cyclin D1 chimeric mRNAs have also been identified in a variety of tumors and appear to lend enhanced stability to cyclin D1, resulting in cellular immortalization [47] and possibly prevention of anoikis [48]. Of note, Trop-2 expression appears to discriminate populations with stem-like activity [49], which may be important for initiation and perpetuation of cancers [50,51].…”
Section: Discussionmentioning
confidence: 99%